Analysis of The Effect of Faith on Subjective Well-Being: (Pilot Study on Muslim Adult In Indonesia) - Izza Himawanti (IQTIDA : Journal of Da'wah and Communication, 2021)
Women on adult phase have deverse development tasks must be exceeded. Including carrying out their roles as mothers and partners, work, work careers and socialities. Various issues about double burden on adult women effects low subjective well-being. The goal of this study was to provide an explanation correlation of increasing faith (in an Islamic perspective) to increase subjective well-being in adult women. This study uses a correlation research method, with cluster random sampling technique. The results showed the correlation coefficient between faith and subjective well-being amounted to 0.524 with a significance level of correlation p = 0.000 (p <0.05). The results of the regression analysis show that the hypothesis was accepted, its mean that there is a positive relationship between faith and subjective well-being. The results of this study can give explanation of psychological dynamics about correlation of increasing faith in the high level of happiness at the stage of adult development.